2019
DOI: 10.5594/jmi.2019.2899230
|View full text |Cite
|
Sign up to set email alerts
|

User-Centric Companion Screen Architecture for Improving Accessibility of Broadcast Services

Abstract: Bridging broadcast and internet services can be difficult, because the system architectures are typically different. Though integrated broadcastbroadband systems that can provide companion screen (CS) services have been standardized, existing systems are television-centric; therefore, it can be difficult for users to easily access broadcast services through mobile applications. Therefore, we propose a CS architecture (CSA) that can be used to tune to specific TV channels and launch broadcast-related applicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…The prototype used in the on-site test was evaluated more positively than that used in the online questionnaire. A prior related work [9] reported that use cases can be evaluated not only by imagining them but also by experiencing them.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The prototype used in the on-site test was evaluated more positively than that used in the online questionnaire. A prior related work [9] reported that use cases can be evaluated not only by imagining them but also by experiencing them.…”
Section: Discussionmentioning
confidence: 99%
“…Similar IBB systems are standardized by the HbbTV 2.0 standard [6] in Europe and ATSC 3.0 [7] in the USA. Additionally, a user-centric companion screen architecture [9] based on Hybridcast was proposed for launching broadcast-related TV applications from mobile or IoT devices to relay TV experiences.…”
Section: Ibb Systemsmentioning
confidence: 99%
See 1 more Smart Citation